Rare case of huge rectal and uterovaginal prol - Laddad, Manisha M.; Kshirsagar, Nitin S.; Nagre, Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
A case of combined genital prolapse and rectal prolapse in a 60-year-old multipara is reported. The treatment of mixed prolapse remains surgical and should be treated the genital prolapse by vaginal hysterectomy with pelvic floor repair and the rectal prolapse by means of the Delorme operation. The mortality and morbidity rates are zero if this operation is used and the relapse rate is only 8 to 11% for the rectal prolapse. It would appear that the two approaches are rarely associated by the authors and would seem to be interesting to reconsider this question by indicating mixed treatment of the two prolapses whenever possible.